An Improved Amperometric Lactose Biosensor Based on Enzyme Nanoparticles - Ahlawat, Jyoti; Aggarwal, Vishakha; Jaiwal, Ranjana; Pundir, C.S. (International Journal of Applied Sciences and Biotechnology, 2022)
A desolvation method was used for the synthesis of β-galactosidase (β-GAL) and glucose oxidase (GOD) nanoparticles (NPs) using ethanol. The enzyme nanoparticles (ENPs) were characterized by transmission electron microscopy (TEM) and Fourier transform Infra-red spectroscopy (FTIR) and were co-immobilized covalently onto surface of polycrystalline Au electrode. An improved amperometric lactose biosensor was constructed using ENPs (β-GALNPs/GODNPs) modified Au electrode as working electrode, Ag/AgCl as reference electrode and Pt wire as auxiliary electrode connected through potentiostat. Cyclic voltammetry (CV) and scanning electron microscope (SEM) were used for the study of working electrode before and after immobilization of ENPs. The biosensor showed maximum current at 0.25V within 5s, at pH 6.5 and 25oC. The limit of detection (LOD) was i.e. 1mg/ml and working range was 1-10 mg/mL. The analytical recovery of added lactose (5 and 10 mg/mL) was 94.73±0.5% and 96.4±0.9%, respectively. Coefficient of variation (CV) within and between batch were